Regulation of Artificial Intelligence in Russia: Eclecticism of Approaches and Actors - E. A. Maslova; N. A. Samoylovaskaya; E. D. Sorokova; A. D. Chekov (Сравнительная политика)
Many observers expect artificial intelligence (AI) to become one of the most important technologies of the 21st century, whose development will be a decisive factor in shaping the future global technological balance of power. A practical confirmation of this statement is the fact that today an increasing number of states are striving to accelerate their national AI development programmes. Russia is one of them, although it is generally not perceived in the West as a potential leader in this emerging competition. At the same time, Russia’s demonstrated ability to build its own successful national IT ecosystem is attracting increased international interest in its national AI development efforts. The purpose of this paper is to outline the contours of these efforts, and to trace the evolution of the regulatory framework and its underlying principles. The authors draw the following conclusions. Russia is developing a flexible and science-based approach to AI and its potential humanitarian impacts, combining its own historical experience with international practices. Strategically, Russia sees the development of national AI as an important means of advancing its economic and technological development in a way that benefits its citizens and businesses, as well as preventing a possible economic and technological slowdown. Significant progress has been made on legal and ethical issues. The focus of Russian efforts in this area is more on soft law norms and self-regulation rather than on prohibitive legislative norms. This approach leaves a lot of room for the development of AI and reduces the possibility of its premature bureaucratisation, which could hinder innovation in the field. There are certain similarities between the Russian and European approaches to AI development and regulation. Human security concerns, data protection and a risk-based approach to the development of AI technologies are prioritised by the state and supranational institutions (respectively) as the main actors responsible for safeguarding the well-being, interests and rights of the citizens.